THE RECONSTRUCTION OF DIVORCE DUE TO MARITAL STATUS UNDER THE UNAUTHORIZED GUARDIAN AS VALUE OF JUSTICE - Abdul Kholiq; Akhmad Khisni (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
A marriage due to an unlawful guardian must be canceled, but often divorce of unlawful guardianship is decided by divorce and talaq, this is not in accordance with the value of justice as in the 5th principle of Pancasila and the Constitution of the Republic of Indonesia. So the authors intend to reconstruct it, by formulating the problem, 1. How is the divorce proceeding in marriage due to the current illegitimate legal status of a guardian? "2. How is the effect of divorce on marriage due to the current unauthorized legal status of guardians ?, 3. What is the legal reconstruction Divorce on marriage due to the status of unlawful guardians of justice value ?, This article uses a qualitative approach, socio legal research, then researchers use the theory of justice as Grand Theory, Law Enforcement as Middle Theory and Legal Protection as Application Theory, As for the reconstruction is to answer the formula The above problem, namely: 1. the implementation of the cancellation of marriage today is when the submission is canceled then the decision is the marriage was decided by divorce, sometimes the filing of divorce / divorce is not investigated in advance whether there is a status of unlawful guardian or not. 2. The answer is the effect of divorce on marriage that there is an illegal guardian's status, if the divorce is decided then the rights demanded back, or other rights not delivered, because if the trial in the form of divorce, usually one of the defendants / requested did not come . Consequently a. The cancellation of marriage must be synchronized with Article 26 of the Marriage Act No. 1 of 1974, which is intended when the cancellation must be in accordance with the juridical reasons, b. For those who already have a marriage certificate, can not be canceled but must be repeated marriage, or ordinary divorce, c.In the cancellation should be examined exactly why the status of guardians is not valid, if due to deliberate from the woman then still said divorce, d.Dalam trial divorce Or talak, if after examined there are unlawful guardians, it must be decided cancellation of marriage not divorce. Keywords: Reconstruction, Divorce, Guardian, Unlawful